1999
DOI: 10.1046/j.1365-2222.1999.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide metabolites in induced sputum: a marker of airway inflammation in asthmatic subjects

Abstract: SummaryBackground and objective The role of nitric oxide (NO) needs to be further clarified in allergic inflammation. This study was designed to investigate the relationships between NO metabolites and eosinophil count, eosinophil cationic protein (ECP), interleukin (IL)-5 in induced sputum from asthmatics. Methods Hypertonic saline-induced sputum was obtained in 25 asthmatic subjects, among which 13 patients were examined before and after anti-asthmatic medications including steroid preparations. Ten normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
1
23
1
Order By: Relevance
“…In aqueous solution, NO reacts rapidly with reactive oxygen species (ROS) to form more stable nitrogen oxides, such as nitrite (NO − 2 ) and nitrate (NO − 3 ) 10 . Increased levels of NO are associated with inflammatory disease states such as asthma, COPD 11 , and cystic fibrosis 12,13 . The increased level of exhaled NO in asthma has been suggested to be due to an increased expression of inducible NO synthase (iNOS) in bronchial epithelium 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous solution, NO reacts rapidly with reactive oxygen species (ROS) to form more stable nitrogen oxides, such as nitrite (NO − 2 ) and nitrate (NO − 3 ) 10 . Increased levels of NO are associated with inflammatory disease states such as asthma, COPD 11 , and cystic fibrosis 12,13 . The increased level of exhaled NO in asthma has been suggested to be due to an increased expression of inducible NO synthase (iNOS) in bronchial epithelium 14 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that NO metabolites were increased in tracheo-bronchial secretions of asthmatic subjects in parallel with asthma severity, and that NO metabolites in sputum are a more valuable indicator for monitoring asthmatic airway inflammation than those in serum [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…And it is known that bronchial hyperresponsiveness is present in on-season seasonal AR [4, 20] and perennial AR [21] without asthma. Several studies have reported the relationship between sputum eosinophils and bronchial responsiveness to methacholine [22, 23], and FEV 1 /FVC ratio [24] in asthmatic subjects. These reports suggest that the airway remodeling partly caused by allergic inflammatory process including eosinophilic inflammation may contribute to the development of bronchial hyperresponsiveness both in seasonal AR and perennial AR patients as well as asthma.…”
Section: Discussionmentioning
confidence: 99%